KERATON SOLO THROUGH LOCAL EYES: UNDERSTANDING TOURIST APPEAL IN CENTRAL JAVA: KERATON SOLO DALAM PERSPEKTIF MASYARAKAT LOKAL: MEMAHAMI DAYA TARIK WISATA DI JAWA TENGAH - Upadewi, Anak Agung Ayu Sri; Albert Bagus Indra Dwinatha; Adelayda Bianca Cenique (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This study examines how the local community perceives Keraton Solo as a cultural tourism attraction, with particular attention to cognitive, affective, and conative dimensions of perception. Understanding local perceptions is essential, as community attitudes play a critical role in the sustainability and authenticity of heritage tourism destinations. This study adopts a quantitative research design, employing a structured questionnaire distributed to 150 local residents living in and around the Keraton Solo area. The collected data were analyzed using the Importance–Performance Analysis (IPA) method, which enables the identification and prioritization of destination attributes based on their perceived importance and actual performance. The findings indicate that environmental quality, ticket pricing, and spatial attractiveness are considered highly important by local residents but are perceived to perform below expectations, suggesting the need for immediate managerial and policy interventions. In contrast, attributes related to guide performance and overall visitor satisfaction are identified as key strengths that should be maintained and enhanced. Interestingly, no attributes were classified as unimportant, highlighting a strong emotional, cultural, and historical attachment of the local community to Keraton Solo. This study is limited to local community perspectives and does not incorporate the views of tourists, policymakers, or other relevant stakeholders. Future research is therefore encouraged to include a wider range of stakeholder perspectives to support more inclusive, participatory, and effective heritage tourism planning and management strategies.